Stability and rheological study on carbon-based nanofluids - Ong, Huei Ruey; Ethiraj, Baranitharan; Rengaraju, Balakrishnaraja; Govindaraj, Swathi; Suresh, Ashwin Raj; Wan Mohd Eqhwan, Iskandar; Khan, Maksudur R.; Muhammad Khairul Anuar, Mohamed; Ridzuan, Ramli; Ilangovan, Shanmuga Sundari; Balakrishnan, Rengesh; Muthusamy, Shanmugaprakash (Informatics Publishing Limited, 2020)
In this study, an organic derived nanofluid has been developed from bio-origin resources. Carbon nanopowder (CNP) is obtained from derived rice husk and was prepared via a simple two-steps thermal process with minimum energy (low temperature and reaction time) using solar assisted plasma furnace. Nanofluids comprised of CNP and EG/water binary mixture has been prepared at various concentration such as 0.02 – 0.10 vol% of CNP. Flow curve of nanofluids showed that at minimum inclusion of CNP improved the stress of the fluid significantly. More to the addition, dynamic viscosity measure possesses that addition of CNP stabilized the properties of the fluid compared to virgin base fluid. Moreover, the stability results showed that the nanofluids stabilized starting from 1 week onwards as evidenced by UV-Visible spectrophotometer analysis. Furthermore, little to no precipitate noticed even after 8 weeks. This work offers greener approach for nanofluids which organic derived and environmentally friendly (very low percentage of nanoparticle, 0.02 vol%)